Activities Used for Interactive Teaching of Magnetism and Electro-Magnetic Induction - Sicam, Victor Arni; van den Berg, Rosea; van den Berg, Ed (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
Some physics teachers use the PC for interactive teaching of introductory physics courses (Sokoloff, 2000; Laws, 1996). To a large extent, this teaching strategy received positive responses from many students and teachers. However, even without the computer, interactive teaching can still be used effectively (Mazur, 1997; Andre, 1993). This paper reports the use of designed activities, without the use of PC's, for interactive teaching of Magnetism and Electro-Magnetic Induction.